2005
DOI: 10.1161/01.atv.0000152611.50953.e2
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin Prevents Vascular Hyperplasia by Inhibiting Phenotype Modulation and Proliferation Through Extracellular Signal-Regulated Kinase 1 and 2 and p38 Mitogen-Activated Protein Kinase Inactivation in Organ-Cultured Artery

Abstract: Objective-We examined the inhibitory mechanisms of fluvastatin on FBS-induced vascular hypertrophy assessed by organ-cultured rat tail artery. Methods and Results-After 5 days of culture with 10% FBS, hyperplastic morphological changes in the media layer were induced. Treatment with 1 mol/L fluvastatin significantly inhibited these changes. In the FBS-cultured arteries, the protein expression ratio of ␣-actin/␤-actin was significantly decreased, indicating the change to synthetic phenotype. Fluvastatin restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
1
24
0
1
Order By: Relevance
“…These data demonstrated that simvastatin inhibited BASMC proliferation via modifying Rho geranylgeranylation. Although several molecules, such as p21 kip1 and extracellular regulated kinase, 32,33 have been reported to mediate the functional roles of Rho signaling in the regulation of cell proliferation, the downstream effectors of active Rho remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data demonstrated that simvastatin inhibited BASMC proliferation via modifying Rho geranylgeranylation. Although several molecules, such as p21 kip1 and extracellular regulated kinase, 32,33 have been reported to mediate the functional roles of Rho signaling in the regulation of cell proliferation, the downstream effectors of active Rho remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrated that simvastatin inhibited BASMC proliferation via modifying Rho geranylgeranylation. Although several molecules, such as p21 kip1 and extracellular regulated kinase, 32,33 have been reported to mediate the functional roles of Rho signaling in the regulation of cell proliferation, the downstream effectors of active Rho remain elusive.During the early phase of cell proliferation, cells undergo swelling because of water influx, which accompanies the uptake of nutrients necessary for cell metabolism. An increase in cell volume will initiate the regulatory volume decrease process through activation of ion (K and Cl) channels and transporters, which activates K and Cl efflux to normalize the cell size.…”
mentioning
confidence: 99%
“…Immunohistochemical staining with BrdU proceeded as described by Sakamoto et al (25). In brief, rats were injected intraperitoneally with 100 mg/kg of BrdU at 48 and 24 h before sacrifice, and 6-μm-thick sections were prepared and stained using the Vector ABC kit (Vector Laboratories Inc., Burlingame, CA, USA).…”
Section: Brdu Labeling Indexmentioning
confidence: 99%
“…Le statine disponibili differiscono per alcune caratteristiche chimico-fisiche (solubilità), farmacocinetiche (assorbimento, legame proteico, metabolismo ed escrezione), farmacodinamiche (potenza relativa ed effetti pleiotropici) [2,[20][21].…”
Section: Profilo Farmacologico E Terapeutico Comparativounclassified